Gambaran Pengetahuan dan Sikap Ibu Hamil Tentang Antenatal Care di Puskemas Aur Duri Kota Jambi Tahun 2018 - Gustina Gustina (Universitas Batanghari Jambi, 2019)
In 2015 mortality rate in indonesia is 305 per 100.000 live births. Compared to other countries the maternal mortality rate in indonesia is still relatively high. Maternal death can be prevented by conducting antenatal care. This study aimed to determine the description of knowledge and the attitude of the pregnant mother about antenatal care at the public health center Aur Duri Jambi city year 2018. This is descriptive research. This study was conducted in Jambi on August - 2018 with populations were pregnant mothers at the public health center Aur Duri Jambi city year 2018 as many as 393 pregnant mothers. Samples used accidental sampling technique as many as 40 pregnant mothers. The collecting of data used interview. Data analyzed as univariate. The findings were obtained the most of pregnant mothers have good knowledge were 27 (67.5%). Most of pregnant mothers have positive attitude were 25 (62.5%) and most of pregnant mothers did antenatal care well that is 36 (90%) pregnant mothers. This study can be concluded the mothers have had good knowledge, a positive attitude and do antenatal care well. For the health personal further enhance counseling about antenatal care that is not only done fpr pregnant mother but also for the community.